2017
DOI: 10.1016/j.scitotenv.2016.10.237
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impacts of milk powder and butter manufactured in the Republic of Ireland

Abstract: The abolition of the milk quota system that was in place in Europe was abolished in 2015, which instigated an immediate increase in milk production in many European countries. This increase will aid in addressing the world's ever growing demand for food, but will incur increased stresses on the environmental impact and sustainability of the dairy industry. In this study, an environmental life cycle assessment was performed in order to estimate the environmental impacts associated with the manufacture of milk p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 11 publications
3
32
0
2
Order By: Relevance
“…Existe um número limitado de artigos disponíveis que discutem ACV de manteiga, entre os quais abordam pegada de carbono (FINNEGAN et al, 2017a), e as fronteiras geralmente compreendem o subsistema industrial. A deficiência de estudos sobre margarina foi ainda maior.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Existe um número limitado de artigos disponíveis que discutem ACV de manteiga, entre os quais abordam pegada de carbono (FINNEGAN et al, 2017a), e as fronteiras geralmente compreendem o subsistema industrial. A deficiência de estudos sobre margarina foi ainda maior.…”
Section: Resultsunclassified
“…De outro modo, existem produtos que têm função concorrente e que podem ser avaliados comparativamente por avaliação de ciclo de vida (ACV), como são os casos da manteiga e da margarina, que são gorduras para espalhar no pão (tecnicamente denominadas de spread). Assim, a ACV também tem sido realizada para casos específicos, como manteiga (FINNEGAN et al, 2017a), leite (FLYSJÖ et al, 2011), leite em pó (FINNEGAN et al, 2017a), bife (FLYSJÖ et al, 2012) e também para comparação (FLYSJÖ et al, 2012;FINNEGAN et al, 2017a;FINNEGAN et al, 2017b). Para os produtos lácteos, a pegada de carbono tem sido o impacto mais estudado (FLYSJÖ et al, 2011), o que pode ser atribuído ao seu grande impacto na pecuária (SEJIAN et al, 2015), como já destacado.…”
Section: Introductionunclassified
“…In the base case analysis, the data from Scottish Government (2011) were used which specified that 7.69 kg raw milk was required to produce 1 kg of milk powder. Finnegan et al (2017) reported two different values: 5.12 and 9.22 kg of raw milk/kg milk powder. These two values are considered as part of the sensitivity analysis and the results are shown in Fig.…”
Section: Amount Of Raw Milk Used To Produce Milk Powdermentioning
confidence: 99%
“…Assessing the environmental impacts at the level of unit operations would be very important and could serve as a basis for evidencing the margins of progress and for system subdivision to properly allocate impacts across the various co-products. Depping et al [9], Santos et al [10], Finnegan et al [7,11], Yan et al [12] and Bacenetti et al [13] to name a few, focus on milk or whey concentration, drying processes, and cheese production. But none of them investigated fractionation processes which are largely used in the dairy industry.…”
Section: Introductionmentioning
confidence: 99%